The Theologian and the Empire: A Biography of José de Acosta (1540–1600) - Prieto, Andrés, author.
1 online resource (420 pages)
Keywords: Although Jesuit contributions to European expansion in the early modern period have attracted considerable scholarly interest, the legacy of José de Acosta (1540-1600) is still defined by his contributions to natural history. The Theologian and the Empire presents a new biography of Acosta, focused on his participation in colonial and imperial politics. The most important Jesuit active in the Americas in the sixteenth century, Acosta was fundamentally a political operator. His actions on both sides of the Atlantic informed both Peruvian colonial life and the Jesuit order at the dawn of the seventeenth century.